Pilihan Hukum Adat dalam Penyelesaian Sengketa di Tanah Papua - Kasim Abdul Hamid (Kyadiren, 2019)
Indonesia is a country with a variety of cultures that stretch from Sabang to Merauke. Cultural diversity makes Indonesia establish more legal systems. Other than the Dutch’s positive legal system, Indonesia’s legal pluralism also applies to the Islamic legal and the traditional law systems which are so-called Indonesia’s original law according to which traditional law experts. Legal centralism (positive law) imposed by the state on the Indonesian people is a form of neglect of other legal systems, especially the traditional law system. Without realizing it, the majority of the Indonesian population are indigenous people from various ethnic groups, but are shackled by legalistic positivism based on written regulations. However, it is different from most Papuan indigenous peoples with a strong desire to make traditional law an independent legal system. The independent traditional law system must be a legitimate desire from the values ​​that live and grow in society. Therefore, traditional law is an option for Papua indigenous peoples in resolving any disputes, because the ideal law is able to satisfy all parties without winning one party and defeating the other.